2019
DOI: 10.1210/js.2019-sat-174
|View full text |Cite
|
Sign up to set email alerts
|

SAT-174 Loss of CEACAM1 in Endothelial Cells Causes Hepatic Fibrogenesis

Abstract: Carcinoembryonic Antigen-related Cell Adhesion Molecule 1 (CEACAM1) has been implicated in physiological processes in the metabolic as well as in the vascular systems, as supported by the cardiometabolic abnormalities associated with insulin resistance that developed in global Ceacam1 null mutants. Given the role of CEACAM1 in maintaining vascular integrity, we aimed at identifying a role for CEACAM1-dependent pathways in endothelial cells in the pathogenesis of hepatic fibrosis. To this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…We have previously shown that hepatic CEACAM1 expression is progressively reduced with advancing fibrosis stages in patients with MASH [15]. Moreover, single cell RNA-sequencing showed lower CEACAM1 expression in hepatocytes and LSECs of patients with fibrosis/cirrhosis [17]. S.M.N.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…We have previously shown that hepatic CEACAM1 expression is progressively reduced with advancing fibrosis stages in patients with MASH [15]. Moreover, single cell RNA-sequencing showed lower CEACAM1 expression in hepatocytes and LSECs of patients with fibrosis/cirrhosis [17]. S.M.N.…”
Section: Discussionmentioning
confidence: 94%
“…As detailed in Supplemental data, fixed liver sections were stained with hematoxylin-eosin (H&E) or with 0.1% Sirius Red stain to evaluate hepatic fibrosis. Images were taken using Nikon Eclipse 90i Microscope and 10 randomly selected high power fields (20X) per sample were imaged with ImageJ (v1.53t) to quantify Sirius Red stain as %area [17].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations